Effect of Bariatric Surgery on Gut Microbiota: A Scientometric Analysis - Miguel Cabanillas-Lazo; Carlos Quispe-Vicuña; Milagros Pascual-Guevara; Maria Eugenia Guerrero; John Barja-Ore; Fran Espinoza-Carhuancho; Frank Mayta-Tovalino (Saudi Journal of Medicine and Medical Sciences, 2024)
Objective: To perform a bibliometric analysis of the scientific production related to intestinal microbiota and bariatric surgery between January 2016 and December 2022.